Influence of a family 29 carbohydrate binding module on the activity of galactose oxidase from Fusarium graminearum - Mollerup, Filip; Parikka, Kirsti; Vuong, Thu V.; Tenkanen, Maija; Master, Emma (Biochimica et biophysica acta, 2016)
Galactose oxidase (GaO) selectively oxidizes the primary hydroxyl of galactose to a carbonyl, facilitating targeted chemical derivatization of galactose-containing polysaccharides, leading to renewable polymers with tailored physical and chemical properties. Here we investigate the impact of a family 29 glucomannan binding module on the activity and binding of GaO towards various polysaccharides. Specifically, CBM29-1-2 from Piromyces equi was separately linked to the N- and C-termini of GaO. Both GaO–CBM29 and CBM29–GaO were successfully expressed in Pichia pastoris, and demonstrated enhanced binding to galactomannan, galactoglucomannan and galactoxyloglucan. The position of the CBM29 fusion affected the enzyme function. Particularly, C-terminal fusion led to greatest increases in galactomannan binding and catalytic efficiency, where relative to wild-type GaO, kcat/Km values increased by 7.5 and 19.8 times on guar galactomannan and locust bean galactomannan, respectively. The fusion of CBM29 also induced oligomerization of GaO–CBM29. Similar to impacts of cellulose-binding modules associated with cellulolytic enzymes, increased substrate binding impeded the action of GaO fusions on more concentrated preparations of galactomannan, galactoglucomannan and galactoxyloglucan; this was especially true for GaO–CBM29. Given the N-terminal positioning of the native galactose-binding CBM32 in GaO, the varying impacts of N-terminal versus C-terminal fusion of CBM29-1-2 may reflect competing action of neighboring CBMs. This study thoroughly examines and discusses the effects of CBM fusion to non-lignocellulytic enzymes on soluble polysaccharides. Herein kinetics of GaO on galactose containing polysaccharides is presented for the first time. •A family 29 carbohydrate-binding module (CBM) was fused to galactose oxidase (GaO).•CBM fusion increased GaO binding to galactose-containing polysaccharides.•C-terminal fusion of CBM29 increased the catalytic efficiency of GaO.•Varying impacts of CBM29 positioning suggests competing action of native CBM32.